2019
DOI: 10.3390/s19061318
|View full text |Cite
|
Sign up to set email alerts
|

RF Energy Harvesting System Based on an Archimedean Spiral Antenna for Low-Power Sensor Applications

Abstract: This paper presents a radiofrequency (RF) energy harvesting system based on an ultrawideband Archimedean spiral antenna and a half-wave Cockcroft-Walton multiplier circuit. The antenna was proved to operate from 350 MHz to 16 GHz with an outstanding performance. With its use, radio spectrum measurements were carried out at the Telecommunication Engineering School (Universidad Politécnica de Madrid) to determine the power level of the ambient signals in two different scenarios: indoors and outdoors. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Nowadays, the most relevant power contributions in the radio spectrum can be found from 0.8 to 5 GHz 26 . In particular, it was pointed out in Reference 27 that more than an 80% of the harvested power had its origin in the mobile bands of 0.8 and 0.9 GHz. Additionally, part of the 5G mobile communications will occupy the frequency bands of 0.6 and 0.7 GHz in the near future 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the most relevant power contributions in the radio spectrum can be found from 0.8 to 5 GHz 26 . In particular, it was pointed out in Reference 27 that more than an 80% of the harvested power had its origin in the mobile bands of 0.8 and 0.9 GHz. Additionally, part of the 5G mobile communications will occupy the frequency bands of 0.6 and 0.7 GHz in the near future 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The most significant power contribution normally comes from mobile network (0.8, 0.9, 1.8, and 2.1 GHz) and WiFi frequency bands (2.4 and 5.2 GHz). Specifically, previous works have demonstrated that most part of the incoming RF power has its origin in mobile bands [3,4,5]. Concretely, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Concretely, Ref. [5] points out that more than an 80% of the power harvested is located in 0.8 and 0.9 GHz frequency bands.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations